Fraud Detection of Financial Statements Using the Beneish M Score Method (Empirical Study on Retail Trading Companies Listed on the Indonesia Stock Exchange 2016-2018): Pendeteksian Kecurangan Laporan Keuangan Menggunakan Metode Beneish M Score (Studi Empiris Pada Perusahaan Perdagangan Eceran Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Sunarjo, Eka Fitria Hanum; Hariyanto, Wiwit (Indonesian Journal of Innovation Studies, 2021)
This study was conducted to determine the retail trading companies listed on the Indonesia Stock Exchange in 2016-2018 which are classified as manipulators and non-manipulators. The type of data used in this research is secondary data. The population in this study are retail trading companies totaling 22 companies and producing a sample of 13 retail trading companies using purposive sampling method. The analytical technique used in this study is a quantitative descriptive technique using the Beneish M Score . The results of the study show that there are 15 retail trading companies that are classified as manipulators in 2016-2018 and have a percentage of 38.46%. The manipulator companies consist of 6 companies in 2016 , 5 companies in 2017 , and 4 companies in 2018 . While the results of the study show that retail trading companies that are classified as non-manipulators in 2016-2018 amounted to 24 companies and had a percentage of 61.54%. The non-manipulator companies consist of 7 companies in 2016, 8 companies in 2017, and 9 companies in 2018.